Immobilization of Multi-Enzymes on Support Materials for Efficient Biocatalysis - Xu, Kongliang; Chen, Xuexiao; Zheng, Renchao; Zheng, Yuguo (Frontiers in Bioengineering and Biotechnology, 2020)
Multi-enzyme biocatalysis is an important technology to produce many valuable chemicals in the industry. Different strategies for the construction of multi-enzyme systems have been reported. In particular, immobilization of multi-enzymes on the support materials has been proved to be one of the most efficient approaches, which can increase the enzymatic activity via substrate channeling and improve the stability and reusability of enzymes. A general overview of the characteristics of support materials and their corresponding attachment techniques used for multi-enzyme immobilization will be provided here. This review will focus on the materials-based techniques for multi-enzyme immobilization, which aims to present the recent advances and future prospects in the area of multi-enzyme biocatalysis based on support immobilization.